Effects of impurity gases on interfaces of the hydrogen-water-decane three-phase system: A square gradient theory investigation - Yafan Yang; Jingyu Wan; Jingfa Li; Weiwei Zhu; Guangsi Zhao; Xiangyu Shang (Capillarity, 2023)
The effects of impurity gases on interfacial characteristics of hydrogen-water-oil three-phase systems are critical to underground H2 storage in depleted oil fields but have not been investigated yet. The square gradient theory calculations with Perturbed-chain statistical associating fluid theory equation of state are carried out to understand the effects of impurity gases (N2, CH4, and CO2) on interfaces of the H2-H2O-n-decane three-phase system under reservoir conditions. Our results obtained from the four-component three-phase systems are compared to the corresponding system without impurity gases. It is found that the all three interfaces (H2-H2O, H2O-C10H22, and H2-C10H22) are greatly influenced by impurity gases. The impurity gases accumulate in all three interfacial regions and have positive surface excesses, which leads to smaller interfacial tensions. The reduction of interfacial tensions depends on the type of impurity gas following this order: CO2 ≥ CH4 > N2. In general, the adsorption of impurity gases weakens the adsorption of other species. However, the adsorption of decane in the H2-H2O interface can be enhanced by impurity gases, which also contributes to the decrease of interfacial tensions. Moreover, the spreading coefficients are mostly negative over the studied temperature and pressure conditions indicating the existence of three-phase contact in the N2/CH4/CO2-hydrogenwater- oil three-phase systems. Document Type: Original article Cited as: Yang, Y., Wan, J., Li, J., Zhu, W., Zhao, G., Shang, X. Effects of impurity gases on interfaces of the hydrogen-water-decane three-phase system: A square gradient theory investigation. Capillarity, 2023, 9(1): 9-24. https://doi.org/10.46690/capi.2023.10.02